DC surface flashover characteristics of G-11CR in vacuum from room temperature to cryogenic temperatures. (July 2019) - Li, Jian; Huang, Rongjin; Wang, Yongguang; Zhang, Chi; Guo, Shibin; Zhang, Hua; Huang, Chuanjun; Wu, Zhixiong; Liu, Huiming; Xu, Dong; Li, Yong; Wang, Wei; et al.
Highlights: A cryostat was constructed for investigating DC flashover. The flashover voltage of G-11CR was tested at three different temperatures. The surface morphologies after flashover present different at different temperatures. Abstract: A helium-free cryostat for DC flashover voltage measurement was constructed. The G-11CR film specimens were tested in vacuum at the temperatures of 293 K, 77 K and 9 K and Weibull distribution was obtained. The results show that the surface flashover voltage of G-11CR film increases as the temperature decreased. The surface flashover voltages did not decrease after 80 times successful flashover and slightly increased as the flashover time increased. Further analysis was performed to investigate the change of G-11CR surface after flashover was characterized by atomic force microscopy (AFM). G-11CR film presented different surface morphologies after 80 times successful flashover at different temperatures.